READING MEANINGS AND SIGNS FROM NATURE THROUGH SUSTAINABLE ARCHITECTURAL DESIGN - Ayub Muktiono (BIOS: Jurnal Informatika dan Sains, 2023)
This research focuses on the interpretation and use of meanings and signs contained in nature through sustainable architectural design principles. In the context of sustainability, this research explores how architects use visual language and natural concepts in building design to create environments that are environmentally friendly and in line with ecological sustainability. This research uses a qualitative approach with descriptive methods. Research results in sustainable architectural design show that the application of principles that include the holistic use of natural meanings and signs can produce buildings that are more environmentally friendly and sustainable. This research confirms that a deep understanding of the natural context, adaptation to the environment, and inspiration from natural forms form the basis for efficient design that suits local site needs. The choice of sustainable materials, which is reflected in these principles, has also been proven to have a positive impact in reducing the environmental footprint and creating more durable buildings. Overall, the results of this research make a significant contribution to the development of a sustainable architectural paradigm, confirming that the integration of natural meanings and signs not only enriches the aesthetics of buildings, but also underlies sustainability and harmony with the natural environment.